A Case Report: Hürthle Cell Carcinoma of the Thyroid Gland - Ağaoğlu, Nazım (Fırat University, 2004)
A case of Hürthle cell carcinoma, diagnosed postoperatively on histopathological examination of the subtotal thyroidectomy tissue material, is presented. Subsequently total thyroidectomy was performed, followed with hormonal replacement therapy and external radiotherapy to the neck.

Bir Olgu Sunumu: Tiroid Bezinin Hürthle Hücreli Karsinomu Ameliyat sonrası subtotal tiroidektomi doku materyalinin histopatolojik incelemesi sonucu Hürthle hücreli karsinomu tanısı konulan bir vaka takdim edilmektedir. Takiben, total tiroidektomi yapıldı, hormon replasmanı ve boyun bölgesine eksternal radiyoterapi ile tedavi edildi.
A Case Report: Hürthle Cell Carcinoma of the Thyroid Gland